Information Transfer Technique in Assessing Listening For Daily Conversation for EFL in Pesantren-Based University - Aries Fachriza; Kristi Nuraini; Muhammad Haikal; Tsalsa Nakita Aina Parahida (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
The assessment was becoming part of teaching activities to measure the learning target. It requires several assessment aspects to gain the language learning achievements of the learners. This article intended to examine the strength of the Information Transfer Technique (ITT) in assessing listening for a daily conversation subject for the students in the first year of students of English Department, the University of Darussalam Gontor which is considered as a Pesantren-based university. The research employed a quasi-experimental with control and experiment groups with a post-test design. Each group consisted of 16 colleagues who were regarded as English Foreign Language learners. Their listening subject was assessed by post-test using the information transfer technique in both control and experimental group.The data were analyzed by an independent sample T-Test. The findings revealed that there was a significant inequality between the mean score of pre and post-test. The mean score of the post-test of learners in the experiment group was significantly higher than that in a pre-test. Furthermore, It is proven that the technique of information transfer is assumed eligible to assess the teaching-learning activities in listening for daily conversation